2020
DOI: 10.1021/acs.langmuir.0c00460
|View full text |Cite
|
Sign up to set email alerts
|

pH/ROS Dual-Responsive Supramolecular Vesicles Fabricated by Carboxylated Pillar[6]arene-Based Host–Guest Recognition and Phenylboronic Acid Pinacol Ester Derivative

Abstract: The pH and reactive oxygen species (ROS) dual-responsive supramolecular vesicle utilizing a novel host–guest molecular recognition between a phenylboronic acid pinacol ester derivative carrying long alkyl chain (PBEC12A) and carboxylated pillar[6]­arene (CP[6]) is developed. The host–guest complexation between CP[6] and PBEC12A was first studied in aqueous solution. PBEC12A was encapsulated within CP[6] forming a stable host–guest complex with a binding constant as high as 106 M–1 order of magnitude. The drivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…CDs are macrocyclic compounds and considered biologically safe. Recent studies have shown that CDs are able to form host–guest complexes by associating with a vast number of commercially available materials. In particular, we demonstrated previously that β-CD-amphiphile complexes can further assemble into diverse structures, including vesicles, tubes, lamellae, helical ribbons, and rhombics . Because 1,4-glycosidic bonds in CDs can be cleaved by α-amylase, , we are able to construct the CD-based molecular assemblies that may serve as a versatile platform for the development enzyme-responsive systems, especially in the construction of enzyme-responsive assemblies that exhibit structural transitions.…”
Section: Introductionmentioning
confidence: 86%
“…CDs are macrocyclic compounds and considered biologically safe. Recent studies have shown that CDs are able to form host–guest complexes by associating with a vast number of commercially available materials. In particular, we demonstrated previously that β-CD-amphiphile complexes can further assemble into diverse structures, including vesicles, tubes, lamellae, helical ribbons, and rhombics . Because 1,4-glycosidic bonds in CDs can be cleaved by α-amylase, , we are able to construct the CD-based molecular assemblies that may serve as a versatile platform for the development enzyme-responsive systems, especially in the construction of enzyme-responsive assemblies that exhibit structural transitions.…”
Section: Introductionmentioning
confidence: 86%
“…[29][30][31] If the assembly of supramolecular building blocks can be manipulated, the sizes and properties of supramolecular vesicles may be controlled. [32][33][34][35] However, understanding the relationship between vesicle size and the corresponding assembly of supramolecular building blocks is still a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…4 With the use of stimuli-responsive bonds, DDSs could stay stable during blood circulation after administration to minimize the side effects caused by drug leakage and achieve TME responsive drug release to ensure high bioavailability. 5,6 To overcome the drawbacks of traditional chemotherapy, several DDSs have been developed, including nanoparticles, [7][8][9][10][11][12][13][14] micelles, 15 and hydrogel. 16 Mesoporous silica nanoparticle (MSNP) based biomaterials are one of the most promising platforms in constructing DDSs, due to their ease of fabrication, mesoporous structure, and a large amount of surface functional groups.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the drawbacks of traditional chemotherapy, several DDSs have been developed, including nanoparticles, 7–14 micelles, 15 and hydrogel 16 . Mesoporous silica nanoparticle (MSNP) based biomaterials are one of the most promising platforms in constructing DDSs, due to their ease of fabrication, mesoporous structure, and a large amount of surface functional groups 17–19 .…”
Section: Introductionmentioning
confidence: 99%